Glycosyltransferases: Methods and Protocols - Brockhausen, Inka (Methods in molecular biology, 2013)
Glycan Microarray Screening Assay for Glycosyltransferase Specificities -- A Fluorescence-Based Assay for Core 1 3Galactosyltransferase (T-synthase) Activity.- Structural and Biochemical Analysis of a Bacterial Glycosyltransferase -- Study of the Biological Functions of Mucin Type Core 3 O-glycans -- Generation of Anti-Sulfated Glycan Antibodies using Sulfotransferase-deficient Mice -- Fluorescent Microscopy as a Tool to Elucidate Dysfunction and Mislocalization of Golgi Glycosyltransferases in COG Complex Depleted Mammalian Cells -- A Practical Approach to Reconstruct Evolutionary History of Animal Sialyltransferases and Gain Insights into the Sequence-Function Relationships of Golgi-Glycosyltransferases -- Fluorescent Lectin Staining of Drosophila Embryos and Tissues to Detect the Spatial Distribution of Glycans during Development -- Photoaffinity Labeling of Protein O-Mannosyltransferases of the PMT1/PMT2 Subfamily -- Enzymatic Analysis of the Protein O-glycosyltransferase, Rumi, Acting toward Epidermal Growth Factor-like (EGF) Repeats -- Enzymatic Characterization of Recombinant Enzymes of O-GlcNAc Cycling -- Antibodies and Activity Measurements for the Detection of O-GlcNAc Transferase, and Assay of its Substrate, UDP-GlcNAc -- In vitro Glycosylation Assay for Bacterial Oligosaccharyltransferases -- In vitro UDP-sugar:Undecaprenyl-Phosphate Sugar-1-Phosphate Transferase Assay and Product Detection by Thin Layer Chromatography -- In vitro O-Antigen Ligase Assay -- Functional Identification of Bacterial Glucosyltransferase WbdN -- Methods for the Pasteurella Glycosaminoglycan Synthases: Enzymes that Polymerize Hyaluronan, Chondroitin, or Heparosan Chains -- Methods for Measuring Class I Membrane-bound Hyaluronan Synthase Activity -- Creation and Characterization of Glycosyltransferase Mutants of Trypanosoma brucei -- Mannose-6-Phosphate: A Regulator of LLO Destruction -- N-Acetylglucosaminyltransferase (GnT) Assays using Fluorescent Oligosaccharide Acceptor Substrates: GnT-III, IV, V, and IX (GnT-Vb) -- A Method for Determination of UDP-GlcNAc: GlcNAcβ1-6(GlcNAcβ1-2)Manα1-R [GlcNAc to Man] β1-4N-acetylglucosaminyltransferase VI Activity -- In vitro Assays of Orphan Glycosyltransferases and their Application to Identify Notch Xylosyltransferases -- In vitro Folding of -1,4Galactosyltransferase and Polypeptide--N-acetylgalactosaminyltransferase from the Inclusion Bodies -- An Assay for 1,6-Fucosyltransferase (FUT8) Activity Based on the HPLC Separation of a Reaction Product with Fluorescence Detection -- Immunodetection of Glycosyltransferases in Gastrointestinal Tissues -- Glycosyltransferases in Chemo-Enzymatic Synthesis of Oligosaccharides -- Tumor Targeting by a Carbohydrate Ligand-Mimicking Peptide -- Glycoengineering of Human Cell Lines Using Zinc Finger Nuclease Gene Targeting - SimpleCells with Homogeneous GalNAc O-glycosylation Allow Isolation of the O-glycoproteome by One-step Lectin Affinity Chromatography -- Generation of Monoclonal Antibodies to Native Active Human Glycosyltransferases.